2013
DOI: 10.2478/ctb-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

EPR Study of Paramagnetic Centers in Human Blood

Abstract: Electron paramagnetic resonance investigations of paramagnetic centers in whole human blood were carried out at 170 K using X-band EPR spectrometer. The study included a group of patients and healthy volunteers. The EPR signals from high spin Fe3+ ions in transferrin (g = 4.2) and Cu2+ ions in ceruloplasmin (g = 2.05) are characteristic of each frozen blood sample. An overview of all recorded spectra revealed in several cases additional lines derived from high spin Fe3+ ions in methemoglobin (g = 5.8 - 6), fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The g factor, assigned to the line formed by the merger of two components with highest amplitudes, is in the g range of 4.14–4.16. Comparison with the literature shows that this signal originates from Fe 3+ in transferrin ( g = 4.2) (Hirota et al 2000 ; Kubiak et al 2013 ; Pocklington and Foster 1977 ), which is also confirmed by the very characteristic shape. Two non-heme iron atoms are in the high-spin state S = 5/2 and their EPR spectrum is characteristic of the compounds in which iron is present in the rhombic symmetry system (Krzyminiewski et al 2011 ; Pinkowitz and Aisen 1972 ) in an octahedral surrounding (Krzyminiewski et al 2011 ).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The g factor, assigned to the line formed by the merger of two components with highest amplitudes, is in the g range of 4.14–4.16. Comparison with the literature shows that this signal originates from Fe 3+ in transferrin ( g = 4.2) (Hirota et al 2000 ; Kubiak et al 2013 ; Pocklington and Foster 1977 ), which is also confirmed by the very characteristic shape. Two non-heme iron atoms are in the high-spin state S = 5/2 and their EPR spectrum is characteristic of the compounds in which iron is present in the rhombic symmetry system (Krzyminiewski et al 2011 ; Pinkowitz and Aisen 1972 ) in an octahedral surrounding (Krzyminiewski et al 2011 ).…”
Section: Resultssupporting
confidence: 64%
“…Electron paramagnetic resonance spectroscopy is an ideal tool for the study of paramagnetic centers in human blood (Krzyminiewski et al 2011 ; Kubiak et al 2013 ). The centers include primarily the molecular complexes containing iron Fe 3+ (transferrin, methemoglobin) or copper Cu 2+ ions (ceruloplasmin).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the g′ = 5.8 band, commonly associated with Fe(III)- heme iron in methemoglobin, suggests that the residual blood57 in the tissue is a minor fraction and it can be neglected in the spectral simulation, due to its different g′ value. Transferrin, a possible candidate for the band observed here40 has a typical linewidth of ~125 G pp at 12 K and a splitting of the g′ = 4.3 peak of ~32 G434457. In contrast, the g′ = 4.3 band observed has a width of 57 ± 2 G pp across all temperatures, and no splitting.…”
Section: Discussionmentioning
confidence: 99%
“…MAENHAUT; DE REUCK, 1989;HALLGREN;SOURANDER, 1958;KREBS et al, 2014). DOBOSZ, 2013;SHIMA et al, 1997;ZECCA et al, 1996); g = 4,28…”
Section: Solução De Ferritinamentioning
confidence: 99%